2003
DOI: 10.1007/s10044-003-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

A brief taxonomy and ranking of creative prototype reduction schemes

Abstract: Various Prototype Reduction Schemes (PRS) have been reported in the literature. Based on their operating characteristics, these schemes fall into two fairly distinct categories -those which are of a creative sort, and those which are essentially selective. The norms for evaluating these methods are typically, the reduction rate and the classification accuracy. It is generally believed that the former class of methods is superior to the latter.In this paper, we report the results of executing various creative P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…Concretely, HYB combines support vector machines with LVQ3 and executes a search in order to find the most appropriate parameters of LVQ3 [31].…”
Section: Prototype Generation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concretely, HYB combines support vector machines with LVQ3 and executes a search in order to find the most appropriate parameters of LVQ3 [31].…”
Section: Prototype Generation Methodsmentioning
confidence: 99%
“…Well known methods for PG are PNN [28], learning quantization vector (LVQ) [29], Chen's algorithm [30], ICPL [27], HYB [31] and MixtGauss [32]. A good study of PS and PG can be found in [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an overall perspective, we now discuss how we are to achieve our goal to reduce the cardinality of the OS-based PRS to be unity for each class. First of all, we know that PRSs can be broadly classified as being "selective" or "creative" [12]. A "selective" PRS yields as its output a set of prototypes which are chosen from the original training points.…”
Section: Introductionmentioning
confidence: 99%